THE ANALYSIS AND RECONSTRUCTION OF LABORATORY ACTIVITIES DESIGN ON THE MATERIAL OF DIFFERENCES BETWEEN ANIMAL AND PLANT CELLS FOR TENTH GRADE STUDENTS - Nuris Fattahillah; Bambang Supriatno; Sri Anggraeni (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2021)
This research aimed to provide an overview of the practicum design regarding the differences between animal cell and plant cell used in Student Worksheet in Banyuwangi Regency. The samples used were 6 Student Worksheets of practicum work on animal and plant cells consisting of 3 Student Worksheets from the education unit level curriculum (hereafter, KTSP) and 3 Student Worksheets from the curriculum 2013. The sampling technique used in this research was purposive sampling. The instruments used were obtained from the Biology Education Lecturers Team of Indonesia University of Education which consisted of relevance aspect, Competency Aspect, practical aspect and knowledge construction analysis of Vee Diagram adapted from Novak & Gowin (1984). The results of the analysis showed the following: 1.) relevance aspect, not in accordance with the demands of Basic Competence, 2.) Competency Aspect, there were no objects or phenomena that could be observed and the ability to think was only limited to C1, 3.) practical aspect, showing that the suitability of the tools , materials and practicum steps still did not meet the practicum standards, and 4.) the knowledge construction of title/objective had not been focused, the object of the phenomenon could not be observed and only a few theories, principles, and concepts could be identified. This shows that the role of Student Worksheet in practicum activities has not been optimal and practicum reconstruction is needed so that practicum activities can run optimally.